2017
DOI: 10.1007/s00125-017-4377-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cell dysfunction in type 1 diabetes: what’s broken and how can we fix it?

Abstract: Type 1 diabetes is an autoimmune disease characterised by the destruction of insulin producing beta cells in the pancreas. Whilst it remains unclear what the original triggering factors for this destruction are, observations from the natural history of human type 1 diabetes, including incidence rates in twins, suggest that the disease results from a combination of genetic and environmental factors. Whilst many different immune cells have been implicated, including members of the innate and adaptive immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 109 publications
(104 reference statements)
1
113
0
Order By: Relevance
“…A) . There is still no consensus on whether T reg cell frequencies correlate with T1D onset . Furthermore, some have argued that T eff cells from diabetic subjects are resistant to suppression by T reg cells , possibly through a STAT‐3‐dependent mechanism .…”
Section: Treg Cell Dysfunction In Human Diseasementioning
confidence: 99%
“…A) . There is still no consensus on whether T reg cell frequencies correlate with T1D onset . Furthermore, some have argued that T eff cells from diabetic subjects are resistant to suppression by T reg cells , possibly through a STAT‐3‐dependent mechanism .…”
Section: Treg Cell Dysfunction In Human Diseasementioning
confidence: 99%
“…People with type 1 diabetes display altered frequencies and function of a number of lymphocyte subsets, as well as different expression levels of surface markers; frequency and suppressive ability of Tregs are reduced in type 1 diabetes [3]. Expression of C-X-C motif chemokine receptor 3 (CXCR3) is reduced on CD3 + T cells in individuals with long-standing type 1 diabetes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, our study indicated that T1D with IPEX is principally caused by Treg dysfunction and can be improved by early intervention with HSCT. Recent studies suggested that reduction in the functional capacity of Treg populations contributes to autoimmune disease development in T1D . We hypothesize that early intervention with HSCT before or following onset of DM can improve several symptoms of IPEX caused by various autoimmunity diseases including T1D.…”
Section: Discussionmentioning
confidence: 88%